Alternative Flexibility Training - David G Behm; Jose Carlos Aragão-Santos; Negar Korooshfard; Saman Hadjizadeh Anvar (International Journal of Sports Physical Therapy)
Over the last approximately 20 years, research has reported on performance impairments following prolonged durations of static stretching. This has led to a paradigm shift towards dynamic stretching. There has also been a greater emphasis using foam rollers, vibration devices, and other techniques. Recent commentaries and meta-analyses suggest that stretching need not be listed as a fitness component as other activities such as resistance training can provide similar range of motion benefits. The commentary aims to review and compare the effects of static stretching and alternative exercises for improving range of motion.